ECOLOGY AND BIOLOGY OF ABUDEFDUF GLAUCUS (CUVIER) (POMACENTRIDAE, PISCES) FROM MINICOY ATOLL, LAKSHADWEEP - Pillai, C S Gopinatha; Mohan, Madan (Indian Journal of Fisheries, 2011)
Studies on the ecology and biology ofsome reef fishes from Lakshadweep wereinititated by the present authors during1981-'83.